Evaluación de Bioinsecticidas para el control de la mosca de la fruta de género Anastrepha. Salache 2021. - Muñoz RiofrIo, Génesis Andrea (2021)
This research was carried out in the Canton Latacunga, in the San Felipe sector, it was carried out at home due to the Covid-19 crisis with the aim of evaluating bioinsecticides with plant species from the Salache sector. In this project, it was applied design (DCA) a completely randomized, with three treatments and without repetitions to make the procedure easier, the life cycle of Anastrepha has been carried out in order to obtain an adult fly to apply the bioinsecticides, Anastrepha It was separated in the pupal stage where a total of 100 pupae were obtained, which were separated in each experimental unit with a total of 25 pupae in each treatment, already in the adult stage the extracts of hemlock, jellyfish and false were made tobacco, that were mixed with molasses, making the bioinsecticides with a dose of 25%. After obtaining the extracts, a Petri dish with a sponge for feeding the fly was placed in each fish tank. 25 cc of bioinsecticide was placed in each sponge. Data collection was performed every 4 hours, resulting in a better daily fly count.